Оцінка інформаційних ризиків при роботі з віртуальним середовищем - Шульга, М. Д. (ХНУРЕ, 2023)
During an information security audit, a fair evaluation of the virtual environment's data protection level is conducted. The audit results reveal the effectiveness of information security and access control measures within the virtual setting, as well as ways to minimize risks when handling confidential information. Evaluating information security risks and employing a holistic risk management approach in a virtual environment enables organizations to better safeguard their virtual infrastructure, maintain data security, and uphold the integrity of their IT systems. By adopting a proactive stance, companies can stay ahead of emerging threats and adjust to evolving developments in the virtualization landscape